5z+(6+2z)=-43

Simple and best practice solution for 5z+(6+2z)=-43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z+(6+2z)=-43 equation:


5z+(6+2z)=-43

We simplify the equation to the form, which is simple to understand
5z+(6+2z)=-43

Remove unnecessary parentheses
+5z+6+2z=-43

We move all terms containing z to the left and all other terms to the right.
+5z+2z=-43-6

We simplify left and right side of the equation.
+7z=-49

We divide both sides of the equation by 7 to get z.
z=-7

See similar equations:

| 9/7t=-7/2 | | 3(a+8)=33.6 | | 1.5x+1=5-2x | | 49/7x60/2x5 | | 15x+(x+2)=10+6x+(-x+3) | | X/p+x/q=a | | 1/2(2t+3)=2/3(6t-1) | | 16=7x | | 3/2x+1=5-2x | | 3=2c-4 | | -16=-4/3X | | 3e-1=15.8 | | 3p=25.8 | | 2x+8=3x+14 | | 2*1/5/4/5 | | 0/47x10x3 | | 3w^2-13w=10 | | 21/5/4/5 | | 6(a+1)=36 | | f/5+5=-7 | | 2x-5+7x=-32 | | m/6-5/8=7/8 | | 4e-8=16 | | -(5y+1)-(4y-6)=3 | | x/2+x/9=5+2 | | (x-y)(x-y)=0 | | 5n^2+12=-19n | | 4x-(5x+2)=4x-27 | | -7x^2-64x-1=0 | | 2x+8-7x+1=3x-1+2x-5 | | 2/3X+1/4Y-5=0 | | 3a-2a+7=3+5 |

Equations solver categories